Pure-helium 3D model atmospheres of white dwarfs - Cukanovaite, Elena; Tremblay, Pier-Emmanuel; Ludwig, Hans-Günter (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. We present the first grid of 3D simulations for the pure-helium atmospheres of DB white dwarfs. The simulations were computed with the co5bold radiat
Gesehen am 13.10.2020